Digital Mobility of Civil Servants: Scientific and Applied Approaches to Ensuring - Byra Ihor R. (Bìznes Inform, 2025)
The article substantiates the importance of implementing digital technologies in the activities of civil servants, which is a key factor and tool for modernizing the public administration system. The article examines the necessity of integrating innovative technologies and developing digital skills among civil servants to enhance the effectiveness of management processes in the State regulation system. The article also generalizes the scientific and practical approaches to ensuring the digital mobility of civil servants, which are critically important for improving the quality of regulatory measures’ development and implementation. The need to implement modern digital technologies is emphasized, such as platforms for electronic document management, mobile applications, cloud solutions, and others, to optimize administrative processes and ensure the transparency and efficiency of public services. An important aspect is the development of digital skills among civil servants, which allows for improved quality of task execution and interaction with businesses and citizens. The issue of ensuring cybersecurity, data protection, and the integration of the latest technologies into State institutions is considered separately, with the relevance of this rapidly increasing due to significant external risks and threats, as well as internal instability or uncertainty in the vectors of the country’s socioeconomic development. An analysis of approaches to improving the regulatory environment and adapting to rapid changes in the technological space is also presented. The necessity for continuous learning and updating the digital competencies of civil servants is emphasized for the effective functioning and improvement of government agencies in the current conditions of global digitalization and digitalization. It is emphasized that successful digitalization is crucial for ensuring a rapid response of governmental structures to contemporary challenges and shocks.